1982
DOI: 10.1001/archinte.142.5.888
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial infections in renal transplant recipients. Seven cases and a review of the literature

Abstract: During an 11-year period, 1,069 patients received renal allografts at the University of Minnesota Hospital, Minneapolis, and infections developed in seven (0.65%) due to mycobacteria (Mycobacterium tuberculosis and M kansasii). The primary infection was in joint or subcutaneous tissue in six patients and pulmonary (miliary) in one. Infections in joint or skin shared common features regardless of the species of Mycobacterium and usually mimicked acute pyogenic bacterial infection; all responded to antimycobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…In the developing world there are unique aspects to the type of infectious complications seen in organ transplantation. For example, high rates of reactivation of M. tuberculosis , or complications such as Trypanosoma cruzii , may occur in organ transplantation ( 13, 14).…”
Section: Comparison Of Frequency Of Infectious Complications Among Thmentioning
confidence: 99%
“…In the developing world there are unique aspects to the type of infectious complications seen in organ transplantation. For example, high rates of reactivation of M. tuberculosis , or complications such as Trypanosoma cruzii , may occur in organ transplantation ( 13, 14).…”
Section: Comparison Of Frequency Of Infectious Complications Among Thmentioning
confidence: 99%
“…2,3 Simultaneously NTM cases were reported in reviews of mycobacterial disease in renal transplant patients, though tuberculosis was the focus with poorer patient outcomes. 4,5 Other case reports focusing on NTM disease appeared in the cancer literature. 6-8 Since that time, tuberculosis has declined significantly in the U.S. and formal population-based epidemiologic studies have demonstrated the burden and increasing incidence of NTM infections and further described the clinical and epidemiologic risk factors for these infections.…”
Section: Introductionmentioning
confidence: 99%
“…NTM infection is not common in the transplant recipient, and disseminated disease due to NTM is particularly rare. However, localized disease has been described in renal, heart, liver, and lung transplant recipients (3, 7–10). The only report of mycobacterial infection in a pancreatic transplant patient involved a spindle cell pseudotumor due to M. tuberculosis (11).…”
Section: Nontuberculous Mycobacterial Infection In the Transplant Recmentioning
confidence: 99%